Refined water security assessment for sustainable water management: A case study of 15 key cities in the Yangtze River Delta, China - Dou, Panfeng; Zuo, Shudi; Ren, Yin; Rodriguez, Manuel J.; Dai, Shaoqing (Journal of environmental management, 2021)
Water security represents ecological security and a policy priority for sustainable development; however, un-gridded assessment results cannot be used to support urban environmental management decisions. This study proposes a systematic framework to obtain a gridded regional water security assessment, which reflects the regional natural resource, based on the index system derived from the Pressure-State-Response (PSR) model and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model. The results were applied to sustainable water management. Using 15 key cities in the Yangtze River Delta (YRD) region as a case study to apply the methodology, we found that the comprehensive water security was relatively high and high-value areas were widely distributed, accounting for about two-thirds of the study area. Low-value areas were mainly distributed in central and eastern regions, such as Shanghai, Suzhou, and Nanjing. There was evidence of a water resource shortage during the twelve-month period studied, particularly in August. The proportions of comprehensive water security in each administrative unit and the differences between simulated and target water quality could be used in the spatial planning and the exploration of payments for ecosystem services (PES) mechanism in county-level or smaller administrative units. Despite the premise requirement and the grid resolution problems of the InVEST model, it can be concluded that our assessment method proves capable of matching spatial and temporal differences in water supply and demand at a fine scale, and results can be used to supply useful information for urban management decision making. [Display omitted] •We propose a water security assessment index using the ecosystem service model InVEST.•The model is applied to the Yangtze River Delta to provide information to water managers.•Spatial and temporal mismatches in water supply and demand are found.•130 counties are classified as 4 types of development zones by the assessment results.•The results can be applied to the allocation of the payment for ecosystem services fund.